Comparative study of xeno-free induction protocols for neural differentiation of human dental pulp stem cells in vitro. (January 2020) - Madanagopal, Thulasi Thiruvallur; Franco-Obregón, Alfredo; Rosa, Vinicius
Highlights: Three differentiation media were used to induce neurogenic differentiation of DPSC. N3 (neurobasal-A media with 20 ng/ml EGF + 40 ng/ml bFGF) increased gene expression of NESTIN, VIMENTIN, ENO2, TUB-3, NF-M and NF-H . Cells treated with N3 presented neuron-like morphology with projections linking different cells. Abstract: Objective: To compare three different xeno-free protocols for neural differentiation of human dental pulp stem cells (DPSC). Methods: DPSC were treated with three different media to induce neural differentiation namely N1 (DMEM for 5 days), N2 (PSC neural induction media for 7 days) and N3 (neural media with B27 supplement, 40 ng/ml bFGF and 20 ng/ml EGF for 21 days). Cell proliferation (MTS assay), morphology, gene (qPCR for NESTIN, VIMENTIN, TUB-3, ENO2, NF-M and NF-H ) and protein expression (flow cytometry) of neurogenic markers were assessed at different time points and compared to untreated cells (DMEM supplemented with 10% FBS). Statistical analysis was performed with global significance level of 5%. Results: N1 and N2 formulations increased the genetic expression of two out of six genes TUB-3, NF-M and TUB-3, NF-H, respectively, whereas N3 elevated the expression of all genes by the late stage. N3 also stimulated protein expression for NESTIN, TUB-3 and NF-H. Cells treated with both N2 and N3 presented neuron-like morphology, decreased proliferation and expression of stemness genes at protocol end point. Conclusion: N3 was the most effective formulation in promoting a neurogenic shift in gene and protein expression. Cells provided with the N3 formulation exhibited neuron-like morphology, elaborating axonal-like projections concomitant with cell cycle withdrawal and reduced expression of stemness genes indicating greater commitment to a neurogenic lineage.